Psikoedukasi Agresi Sebagai Upaya Untuk Meningkatkan Pengetahuan Anti-Agresi Pada Siswa SMPN ABC Surabaya - Bungaran, Daniel Reyonald; Cahyanti, Ika Yuniar (Journal of Research and Measurement in Psychology: JPPP, 2020)
This psychological intervention aims to increase the knowledge of anti-aggression among students in class “X”, SMPN ABC, Surabaya by giving anti-aggression psychoeducation. This research is a pre experimental research, one group pretest-posttest design. Whole sampling was used as sampling technique with 39 students as sample. The knowledge of anti-aggression was measured by pretest-posttest questionnaire made by researcher. Data is analyzed by using paired samplet-test. The result of intervention showsthat there is a significant difference between pretest and posttest score of knowledge of anti-aggression (p =0.000 <0.05)after the delivery of psychoeducation